Autoantigens PLA2R and THSD7A in membranous nephropathy share a common epitope motif in the N-terminal domain. Issue 106 (January 2020) - Fresquet, M.; Rhoden, S.J.; Jowitt, T.A.; McKenzie, E.A.; Roberts, I.; Lennon, R.; Brenchley, P.E.
Abstract: Patients with membranous nephropathy have autoantibodies against PLA2R (up to 80%), or THSD7A (up to 2%). We previously described the immunodominant epitope within PLA2R but epitopes in THSD7A are still unknown. To find anti-THSD7A sera for this study, we screened 1843 sera from biopsy-proven MN patients by ELISA and identified 22 sera as anti-THSD7A positive representing 1.2% of MN cases. Anti-THSD7A positive sera were further characterized by western blotting and slot blotting on THSD7A protein fragments and peptides. Real time interaction analyses and antibodies off-rate could be reliably determined using bio-layer interferometry. A signature motif in the N-terminal domain of THSD7A (T28mer) with sequence homology to the major PLA2R epitope (P28mer) was identified. B-cell epitope prediction analysis and homology modelling revealed this sequence to be antigenic and surface available suggesting it is accessible for the antibody to bind. All ten selected sera bound to the T28mer confirming this sequence as a dominant epitope in THSD7A. Reactivity to this sequence was lost following kallikrein protease cleavage within the predicted epitope. Importantly, cross-reactivity of both PLA2R and THSD7A autoantibodies was observed at the peptide but not the protein level. We propose that this common motif shared by both autoantigens could be an epitope involved in the initial B-cell triggering event in MN. Highlights: Membranous nephropathy (MN) is an autoimmune disease characterized by the presence of autoantibodies to podocyte receptors. The two main antigens are PLA2R in 80% of patients and THSD7A in approximately 2% of the cases. A novel epitope sequence in THSD7A has high similarities with the PLA2R dominant epitope. This shared motif is a potential common initiating epitope of autoimmunity in MN.